Picosecond charge localization dynamics in CH₃NH₃PbI₃ perovskite probed by infrared-activated vibrations - Stallhofer, Klara (2022)
Hybrid metal halide perovskites exhibit well-defined semiconducting properties and efficient optoelectronic performance considering their soft crystal structure and low-energy lattice motions. The response of such a crystal lattice to light-induced charges is a fundamental question, for which experimental insight into ultrafast time scales is still sought. Here, we use infrared-activated vibrations (IRAV) of the organic components within the hybrid perovskite lattice as a sensitive probe for local structural reorganizations after photoexcitation, with femtosecond resolution. We find that the IRAV signal response shows a delayed rise of about 3 ps and subsequent decay of pronounced monomolecular character, distinguishing it from absorption associated with free carriers. We interpret our results as a two-step carrier localization process. Initially, carriers localize transiently in local energy minima formed by lattice fluctuations. A subpopulation of these can then fall into deeper trapped states over picoseconds, likely due to local reorganization of the organic molecules surrounding the carriers.